VISUAL MEDIA-BASED ENGLISH TEACHING AT THE 11 TH GRADE OF AL-FALAH AL-ISALMEE SCHOOL, BANNANG SATA DISTRICT, YALA-THAILAND - Basuni Basuni (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
Al-Falah Al-Islamee School is located in Bannang Sata District, Yala Province- Thailand. Al-Falah is a school located in the border area between southern Thailand and Malaysia. This school is located in the village but has great expectations to be able to compete with other schools. One of the efforts to improve the quality of education is starting from teaching. Teaching English in Al-Falah is very important, this is done to prepare students to be able to communicate well. The problem of students in learning English is that they cannot be active and consider English difficult. Of course, it is the teacher's responsibility to be able to make the students understand by teaching them. The purpose of this study was to find out how the activity and effectiveness of English learning by Al-Falah Al-Islamee teachers based on planning stages of teaching, stages of teaching implementation, and teaching evaluation stage. In this case, the teacher of Al-Falah Al-Islamee has chosen visual media-based English teaching to make the atmosphere of student learning active, creative, and effective. In other words, students can easily understand English language learning. The research method used is a qualitative descriptive method. The research subjects are principals, English teachers, and students. The object in this study is a learning model using visual media-based English teaching. The data collection technique carried out in this study was a triangulation of data namely observation, interviews, and documentation. The data analysis technique in this study was the reduction of display data and verification and then analyzed using qualitative descriptive analysis. The result of this study are that the development of learning using visual media-based English teaching is very effective, this can be seen from students who enthusiastically follow classroom learning and confidence in telling the events of the text. So that these learning activities support in achieving student learning achievements.